2021
DOI: 10.1080/20008198.2021.1978669
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in post-traumatic stress disorder in a high adversity cohort of South African adolescents: an examination of depressive symptoms, age, and trauma type as explanatory factors

Abstract: Background Evidence from high-income countries (HICs) has documented a higher rate of post-traumatic stress disorder (PTSD) in females than males. However, data are limited on sex differences in PTSD from low- and middle-income countries (LMICs), despite particularly high levels of trauma experienced by LMIC youth. Objectives In a sample of adolescents from an impoverished South African community, we examined sex differences in PTSD, as well as co-occurring depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…Findings that female children exhibit significantly greater symptom severity than males in the acute aftermath of trauma are in line with current adult and adolescent literature. A consensus has now emerged that females are at a greater risk of PTSD regardless of the type or severity of the trauma, and international context (Christiansen & Berke, 2020; Hiscox et al, 2021; Kessler et al, 1995; Olff et al, 2007; Tolin & Foa, 2006). However, this study identified age as a significant moderating variable in children, whereby sex differences in the presentation of PTSD increase with the age of exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings that female children exhibit significantly greater symptom severity than males in the acute aftermath of trauma are in line with current adult and adolescent literature. A consensus has now emerged that females are at a greater risk of PTSD regardless of the type or severity of the trauma, and international context (Christiansen & Berke, 2020; Hiscox et al, 2021; Kessler et al, 1995; Olff et al, 2007; Tolin & Foa, 2006). However, this study identified age as a significant moderating variable in children, whereby sex differences in the presentation of PTSD increase with the age of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, all linear regression models accounted for clustering based on a study, which appropriately generates larger standard errors with subsequently wider confidence intervals and more conservative p values. Second, the prevalence or severity of other mental health symptoms such as depression and comorbid Axis 1 disorders were not available, which would have provided confirmation on the independent effects of PTSS (Salk, Hyde, & Abramson, 2017) although previous work suggests co-occurring depressive symptoms are unlikely to explain sex differences in child PTSS (Haag et al, 2020; Hiscox et al, 2021). We also harmonised PTSD symptoms across studies but did not harmonise the dichotomisation of scores based on probable PTSD diagnoses; thus, replication of these results based on the presence/absence of diagnosed PTSD is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 3 years, evidence has emerged on specific biological mechanisms that may be driving sex-related patterns in individuals with PTSD. The majority of studies identified in this review, however, were conducted in high-income countries; biological contributors and consequences of adult PTSD will additionally need to be examined in low-to-middle income country settings [ 69 ]. Few studies have also been primarily designed, and statistically powered, to investigate sex differences in PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence was relatively consistent in showing symptom improvement [35 ▪ ]. Although school-based interventions have typically been delivered following mass trauma they may also be suitable in communities where the prevailing level of child trauma exposure is high [36].…”
Section: Treatment Deliverymentioning
confidence: 98%